Development of Safe and Non-Self-Immunogenic Mucosal Adjuvant by Recombinant Fusion of Cholera Toxin A1 Subunit with Protein Transduction Domain - Byoung-Shik Shim; In Su Cheon; Eugene Lee; Sung-Moo Park; Youngjoo Choi; Dae-Im Jung; Eunji Yang; Jung-ah Choi; June Young Chun; Jae-Ouk Kim; Cheol-Heui Yun; Cecil Czerkinsky; et al. (Journal of Immunology Research)
Potential use of cholera toxin (CT) as a mucosal vaccine adjuvant has been documented in a variety of animal models. However, native CT is highly toxic to be used as a mucosal adjuvant in humans. Here, we demonstrate a new approach to generate a mucosal adjuvant by replacing the B subunit of CT with HIV-1 Tat protein transduction domain (PTD), which efficiently delivers fusion proteins into the cell cytoplasm by unspecific binding to cell surface. We compared the adjuvanticity and toxicity of Tat PTD-CTA1-Tat PTD (TCTA1T) with those of CT. Our results indicate that intranasal (i.n.) delivery of ovalbumin (OVA) with TCTA1T significantly augments the OVA-specific systemic and mucosal antibody responses to levels comparable to those seen with CT adjuvant. Moreover, in vivo cytotoxic T lymphocyte activity elicited by TCTA1T was significantly higher than that elicited by a mutant TCTA1T (TmCTA1T) lacking ADP-ribosyltransferase function. In addition, coadministration of influenza M2 protein with TCTA1T conferred near complete protection against lethal influenza virus challenge. Importantly, TCTA1T, in contrast to CT, did not induce serum IgG antibody responses to itself and was shown to be nontoxic. These results suggest that TCTA1T may be a safe and effective adjuvant when given by mucosal routes.